A single mutation may contribute to accelerated evolution of SARS-CoV-2 toward Omicron - Xiaoyuan Lin; Zhou Sha; Chunlin Zhang; Julia M. Adler; Ricardo Martin Vidal; Christine Langner; Beibei Fu; Yan Xiong; Meng Tan; Chen Jiang; Hao Zeng; Xiaokai Zhang; et al. (Nature Communications)
Abstract How SARS-CoV-2 Omicron evolved remains obscure. T492I, an Omicron-specific mutation encountered in SARS-CoV-2 nonstructural protein 4 (NSP4), enhances viral replication and alters nonstructural protein cleavage, inferring potentials to drive evolution. Through evolve-and-resequence experiments of SARS-CoV-2 wild-type (hCoV-19/USA/WA-CDC-02982585-001/2020, A) and Delta strains (B.1.617) with or without T492I, this study demonstrates that the NSP4 mutation T492I confers accelerated phenotypic adaption and a predisposition to the emergence of SARS-CoV-2 Omicron-like variants. The T492I-driven evolution results in accelerated enhancement in viral replication, infectivity, immune evasion capacity, receptor-binding affinity and potential for cross-species transmission. Aside from elevated mutation rates and impact on deaminases, positive epistasis between T492I and adaptive mutations could potentially mechanistically facilitate the shifts in mutation spectra and indirectly determines the Omicron-predisposing evolution. These suggest a potentially important role of the driver mutation T492I in the evolution of SARS-CoV-2 Omicron variants. Our findings highlight the existence and importance of mutation-driven predisposition in viral evolution.